Perjalanan Psikologi Tokoh Utama dalam Cerpen Keluarga M Karya Budi Darma: Analisis Psikologi Freudian - Nurfadillah, Atik Azzahra (RUANG KATA: Journal of Language and Literature Studies, 2023)
This research aims to determine the psychological journey of the main character in the short story collection People of Bloomington in the short story Keluarga M by Budi Darma, by applying Freud's literary psychology approach. The character investigated is "I" as the central character in the story, who is faced with quite complex internal and external conflicts with the people around him. The method used in this research is a descriptive qualitative method. The theory of inner conflict and personality structure, namely in the form of Id, Ego, Superego then produces a basis for interpreting the actions and emotional reactions of characters to situations and other characters in the story. In short, this research shows that the personality aspect in the form of ego can dominate all of an individual's behavior and actions. The research results show that Freud's theory provides insight into understanding the complexity of individual psychology, especially the main character in the story. Keywords: Keluarga M, Freud's Psychology, Inner Conflict, Main Characters.